Proceedings of the Conference on Noise Suppression NOISE CONTROL 85 - ENGEL, Zbigniew (Archives of Acoustics, 1985)
Several days after the INTER NOISE 85 Conference the International Conference on Noise Suppression – NOISE CONTROL 85 was held from the 24-th to the 27-th of September 1985 in Cracow. It was organized by the Committee on Acoustics of the Polish Academy of Sciences, Commission of Acoustics of the Hungarian Academy of Sciences, Institute of Mechanics and Vibroacoustics of the Academy of Mining and Metallurgy in cooperation with the Institute of Structural Engineering, the Central Institute of Work Protection and the Noise Control League.